Analisis Kebutuhan E-Comic Berbasis Perubahan Konseptual pada Materi Tata Surya Kelas VII MTS - Rina Aprilia; Ida Sriyanti; Apit Fathurohman (Jurnal Penelitian Pendidikan IPA, 2026)
Students often find the solar system challenging due to its abstract nature and vast spatial and temporal scales. Students are unable to directly observe phenomena such as planetary revolution or the internal structure of the sun in the classroom. This often leads to misconceptions or incomplete conceptual understanding. For example, many students still assume that planetary orbits are perfectly circular or misunderstand the causes of seasonal changes. This study aims to analyze the need to develop an e-comic as a conceptual change-based learning medium for seventh-grade students of Islamic Junior High Schools (MTs). Conceptual change is an important approach in science learning that helps students replace incorrect initial concepts with correct scientific concepts. Using a needs analysis method, 51 students responded to various questions posed to identify gaps in students' understanding of the solar system concept. Data were collected through observations, interviews with teachers, and student questionnaires. The results indicate that a conceptual change-based e-comic is highly needed as an alternative learning medium that can facilitate a more effective and enjoyable learning process. This research provides a strong basis for the development of e-comic media that is appropriate to the characteristics of grade VII MTs students in understanding solar system material.